2022
DOI: 10.1186/s12862-022-02042-5
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of cribellate orb-weaver capture thread spidroins

Abstract: Background Spiders have evolved two types of sticky capture threads: one with wet adhesive spun by ecribellate orb-weavers and another with dry adhesive spun by cribellate spiders. The evolutionary history of cribellate capture threads is especially poorly understood. Here, we use genomic approaches to catalog the spider-specific silk gene family (spidroins) for the cribellate orb-weaver Uloborus diversus. Results We show that the cribellar spidroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 109 publications
2
22
2
Order By: Relevance
“…S1 ). This differs somewhat from the results reported by Correa-Garhwal et al [ 43 ], which identified 10 tandem repeats. As with previous reports on the structure of AcSp [ 26 , 108–110 ], we also found that the repeats are remarkably well homogenized.…”
Section: Data Descriptioncontrasting
confidence: 99%
See 3 more Smart Citations
“…S1 ). This differs somewhat from the results reported by Correa-Garhwal et al [ 43 ], which identified 10 tandem repeats. As with previous reports on the structure of AcSp [ 26 , 108–110 ], we also found that the repeats are remarkably well homogenized.…”
Section: Data Descriptioncontrasting
confidence: 99%
“…We found 12 full-length candidate sequences, including at least 1 candidate for each of the 7 types of spidroin used by cribellate orb-weavers, as well as candidate sequences for the ampullate spidroin (AmSp) and 2 proposed paracribellar spidroins (Sp_vA and Sp_vB) recently reported by Correa-Garhwal et al [ 43 ]. There were no gaps in the assembly interrupting our candidate spidroin sequences with the exception of Sp_vA.…”
Section: Data Descriptionmentioning
confidence: 88%
See 2 more Smart Citations
“…pilipes and T . clavipes [ 51 ] and is present in some MaSp repeat sequence of Uloborus diversus , a distantly related cribellate orb-weaver [ 128 ]. Given its prominence in Argiope and widespread taxonomic distribution, GQQGPG may represent a central functional motif whose expansion is tied to changes in initial fiber crystallinity and disorder.…”
Section: Discussionmentioning
confidence: 99%